PENERAPAN TEKNOLOGI INFORMASI PENDUKUNG KORESPONDENSI DAN PELAPORAN DOKUMEN PADA GURU PAUD DI KOTA BATAM - Amrizal, Amrizal; Rika Harman; Nopriadi, Nopriadi (PUAN INDONESIA, 2024)
The implementation of community service activities that will be carried out in the form of correspondence training and document reporting using applications in Microsoft Word is very useful for PAUD teachers in the city of Batam, because this capability will make it easier for PAUD teachers in the city of Batam in terms of correspondence. and reporting as well as increasing creativity in collaborating and abilities in the administration of the workplace. community service activities by applying the method of making activity reports, correspondence and correspondence as well as making information technology-based reporting formats by utilizing existing applications in Microsoft Word with the hope that this activity will be able to provide creativity, optimize existing IT facilities and increase human capabilities and resources especially for individual PAUD teachers in the city of Batam.